Management information systems : - Laudon, Kenneth C. (Pearson, 2012)
The Editorial team at Pearson has worked closely with educators around the world to include content which is especially relevant to students outside the United States. Laudon and Laudon continue to define the MIS course with their latest comprehensive text. Management Information Systems provides comprehensive and integrative coverage of essential new technologies, information system applications, and their impact on business models and managerial decision making in an exciting and interactive manner